Upaya Peningkatan Kinerja Arsiparis di Perguruan Tinggi Keagamaan - Hayati, Afita Nur (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
The purpose of this study is to describe the improvement in the capacity of the State Islamic University of Sultan Aji Muhammad Idris (UINSI) Samarinda educational staff. This study focuses on the Special Functional Department (JFT) of the Senior Records Manager during their new post-equalization activity. A qualitative method was taken in this study. Case studies are selected to study spesific cases such as individuals, groups, institutions, or communities more intensively. This is because case studies make it possible to pinpoint crucial elements, procedures, and even relationships. JFT Senior Records Manager from various UINSI Samarinda units were the informants who were interviewed. According to the study's findings, JFT Senior Records Manager did not have basic knowledge whatsoever related to the functional duties given due to the process of enforcement. This study's conclusion is that education and training is a way to improve performance. The UINSI Samarinda educational staff offers formal master's-level coursework in general education, but the program of study is not specifically related to archivism. However, training in accordance with the field of responsibility could not be performed in an ideal manner to meet the requirements of his functional department.